Safety and efficacy after switch to a saquinavir-containing antiretroviral regimen in protease inhibitor pretreated HIV-positive patients - Stephan C; Jaeger H; Carganico A; Knecht G; Lutz T; Mayr C; Mosthaf FA; Koeppe S; Mueller M; Wolf E; Tappe A; Wellmann E; et al. (European Journal of Medical Research, 2010)
Abstract Objective The RAINBOW survey is a multinational observational study assessing the tolerability and efficacy of ritonavir-boosted saquinavir (SQV/r), using the 500 mg film-coated SQV formulation, in routine clinical practice. This analysis presents data from the German subgroup of protease inhibitor (PI)-pretreated, but SQV-naïve patients. Methods Multicenter, prospective, open-label, 48 week cohort study. Efficacy assessments included the proportion of patients with HIV-1 RNA < 50 and < 400 copies/mL and changes in CD4 cell count from baseline to week 48. Tolerability assessments included changes in liver enzymes and lipid levels from baseline to week 48. Results A total of 426 patients were included in the analysis. The proportion of patients with HIV RNA levels < 50 copies/mL at week 48 was 60.3% (compared with 31.7% at switch to SQV/r) (intent-to-treat, last observation carried forward analysis). After 48 weeks, median CD4 count increased by +61 cells/mm3 from baseline (p < 0.01) and 60.3% of patients achieved HIV-1 RNA < 50 copies/mL. Median changes in fasting triglyceride levels (stratified according to baseline level) at week 48 were: +14 mg/dL (IQR -8; 57) for patients with baseline triglyceride < 200 mg/dL; -50 mg/dL (IQR -139; 0) for baseline triglyceride 200-750 mg/dL, and -656 mg/dL (IQR 1024; 0) for baseline triglyceride > 750 mg/dL (p < 0.01 for all). Median changes in fasting total cholesterol (TC) levels (stratified according to baseline) were +16 mg/dL (IQR -3; 43) for patients with baseline TC < 200 mg/dL (p < 0.01), -3 mg/dL (IQR -25; 25) for baseline TC 200-300 mg/dL (p = 0.4), and -47 mg/dL (IQR -87; -4) for baseline TC > 300 mg/dL (p < 0.01). No significant changes in liver enzymes or bilirubin were observed. SQV treatment was discontinued in 22% of patients, 6% due to side effects. Conclusions These data confirm the efficacy and tolerability of SQV/r in PI-experienced, SQV-naïve patients treated in a real-life clinical setting. Of particular relevance are the improvements in triglycerides and TC levels observed in patients with baseline grade III-IV elevations.